ARSIP DAN RETENSI ANALISIS ISI JADWAL RETENSI ARSIP KEMENTERIAN KETENAGAKERJAAN: Array - Suprayitno Suprayitno; Sumarno Sumarno (Arsip Nasional Republik Indonesia, 2018)
This paper aims to find out how many records in the Ministry of Manpower's Records Retention Schedule (JRA) that are to be appraised as archival records or in regular cases having permanent value. By using content analysis method, the results of this study state that there are 177 records series (26.62%) of Ministry of Manpower's Retention Schedule which are stated as permanent. The theoretical implications are against archival theory in general which states that the number of archival records in an organization are roughly 1% to 10%. This high percentage can be attributed to Derrida's ‘archive fever’ concept that both records managers and archivists are afraid of losing memory from the Ministry of Manpower's archival records. This effort to give meaning is temporary because it departs from latest findings and is a limitation of quantitative content analysis methods. It is a must to develop further research among others by using phenomenological method.